Application of marker‐assisted backcross to introgress Bph3, Bph14 and Bph15 into an elite indica rice variety for improving its resistance to brown planthopper. Issue 3 (25th April 2016) - Hu, Wei; Xiao, Hanxiang; Hu, Kan; Jiang, Yijun; Zhang, Yang
Abstract: To improve brown planthopper ( Nilaparvata lugens Stål; BPH) resistance of an elite indica cultivar of South China, Hemeizhan (HMZ), we applied marker‐assisted backcross (MABC) to incorporate three BPH‐resistance genes ( Bph3, Bph14 and Bph15 ) into the genetic background of HMZ. In the third backcross (BC3 ) generation, we obtained near‐isogenic lines ( Bph3 ‐NIL, Bph14 ‐NIL, Bph15 ‐NIL and Bph14 + Bph15 ‐NIL) with more than 96% recovery of recurrent parent genome, and pyramided lines ( Bph3 + Bph14 ‐PYL, Bph3 + Bph15 ‐PYL and Bph3 + Bph14 + Bph15 ‐PYL) with more than 89% recovery of recurrent parent genome. These lines showed stronger resistance against BPH than HMZ at seedling and booting stages. The rank of resistance gene effect was Bph3 + Bph14 + Bph15 ≥ Bph3 + Bph15 ≥ Bph3 +Bph14 ≥ Bph14 + Bph15 ≥ Bph3 ≥ Bph15 ≥ Bph14 > none. Compared with HMZ, only Bph3 + Bph14 + Bph15 ‐PYL had a significant difference in yield per plant, and the lines carrying Bph3 had higher amylose contents, indicating that Bph3 was tightly linked to Wx a allele. These improved lines are good intermediate sources of broad‐spectrum and durable BPH resistance to improve other indica cultivars. Our results demonstrate that MABC is a very efficient approach to improve BPH resistance of elite rice cultivar.